El poder del posicionamiento. Caso Nirsa - Chedraui, Lorraine (2017)
The objective of this article is to evaluate the importance of generating brand positioning based on the analysis of the Nirsa case of Guayaquil -Ecuador, with its canned tuna products of the Real brand. A documentary research and an interview with the Sales Manager of the company Nirsa were carried out. The main results obtained were as follows: the benefits of the product and highlight its most outstanding characteristics, define the distinctive place in the market and make the brand a solid basis of competitive advantage, this contributes to increased sales, of the reputation of a brand, and helps new product lines in the market more easily